Management Education and Development - Herbert, Theodore T. (Academy of Management Review, 1976)
The article reviews several books related to management education, including “The Case Method at the Harvard Business School,” edited by Malcolm P. McNair, “Training By Objectives: An Economic Approach to Management Training,” by George S. Odiorne, and “Dynamic Management Education,” by Allen A. Zoll.